Progress in cryptology - INDOCRYPT 2016 : 17th International Conference on Cryptology in India, Kolkata, India, December 11-14, 2016, proceedings /: 17th International Conference on Cryptology in India, Kolkata, India, December 11-14, 2016, proceedings. (2016) - Unknown
No abstract available